FREQUENCY OF ADVERSE OBSTETRIC AND FETAL OUTCOME AMONG OVERWEIGHT AND OBESE WOMEN - Bokhari, Nadia; Hayat, Zartaj; Akhtar, Nosheen; Asmat, Saadia (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the frequency of adverse fetomaternal outcome in obese and overweight pregnant women. Methodology: This cross sectional study was conducted in the Department of Obstetrics and Gynecology, Fauji Foundation Hospital, Rawalpindi from 1st October 2016 to 30th September 2017. Total 200 pregnant females with body mas index (BMI) >25 kg/m2 and gestational age of up to 20 weeks were selected by convenience sampling. Patients were followed up for maternal antenatal, natal, postnatal and fetal complications. Hospital Medix TM was used for data collection. Results: In our study, 20% of women were overweight, 30% were obese while 50% were morbidly obese. These women had high frequency of miscarriages (8.5%), gestational diabetes mellitus (33%), pregnancy induced hypertension (25%), preeclampsia (16%), eclampsia (2%), preterm delivery (18.5%) and postdate pregnancies (10.5%). The rate of induction of labour was 36.7% among these women. Instrumental delivery rate was 6.5%, while cesarean section rate was 38%. Postpartum hemorrhage was noted in 5.5%, while wound infection, endometritis and deep venous thrombosis (DVT) affected 7%, 2% and 0.5% respectively. Regarding fetal complications, congenital malformations were seen in 4%, intrauterine death in 4%, macrosomia 13%, shoulder dystocia in 2%, low birth weight in 5.5%, neonatal intensive care unit admissions in 21.5% and early neonatal death in 5.5%. Conclusion: Obese and overweight pregnant women had increased frequency of maternal and fetal complications.